2014 36th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2014
DOI: 10.1109/embc.2014.6944497
|View full text |Cite
|
Sign up to set email alerts
|

An integrated neuro-robotic interface for stroke rehabilitation using the NASA X1 powered lower limb exoskeleton

Abstract: Stroke remains a leading cause of disability, limiting independent ambulation in survivors, and consequently affecting quality of life (QOL). Recent technological advances in neural interfacing with robotic rehabilitation devices are promising in the context of gait rehabilitation. Here, the X1, NASA's powered robotic lower limb exoskeleton, is introduced as a potential diagnostic, assistive, and therapeutic tool for stroke rehabilitation. Additionally, the feasibility of decoding lower limb joint kinematics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…“Manufacturers” are companies (ReWalk, Indego, Ekso, etc. ), institutions (NASA X1,14 Kinesis,63 etc. ), and many other labs and startups whose prototypes are still in early development.…”
Section: Regulations and Standardsmentioning
confidence: 99%
“…“Manufacturers” are companies (ReWalk, Indego, Ekso, etc. ), institutions (NASA X1,14 Kinesis,63 etc. ), and many other labs and startups whose prototypes are still in early development.…”
Section: Regulations and Standardsmentioning
confidence: 99%
“…Stroke etiology was reported in 92 cases: 72 of which were ischemic in origin, 18 were hemorrhagic, and two were ischemic/hemorrhagic. Six studies did not provide information related to stroke type (Ping et al, 2013 ; He et al, 2014 ; Androwis et al, 2018 ; Sloot et al, 2018 ). The time from stroke to study participation was reported for 98 patients, with the majority ( N = 57) recruited in the chronic phase of stroke.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies identified the participants as “walkers” but did not specify the level of assistance required, if any (Chisari et al, 2015 ; Srivastava et al, 2016 ; Sloot et al, 2018 ). Other studies described the participants' mean motor subscale score of the Functional Independence Measure (Androwis et al, 2018 ) [26 ± 4; where 13–38 indicate low scores for motor independence as guided by Itaya et al ( 2017 )], the Fugl–Meyer Lower Limb Scale (He et al, 2014 ) [12/34; where a cutoff score of <21 indicates lower mobility levels, as guided by Kwong and Ng ( 2019 )], or strength of the lower limb tibialis anterior muscles of <4 on the MRC scale (Gandolla et al, 2018 ) or specified the level of assistance required to walk (Hesse et al, 2010 ; Ping et al, 2013 ). Two studies did not address the participants' walking status (Fan and Yin, 2013 ; Contreras-Vidal et al, 2018 ); however, one of these studies used the 6 MWT as a baseline score.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations